SOCIAL PROBLEMS AND ENVIRONMENT - Tiwari, Neeta (International Journal of Research -GRANTHAALAYAH, 2015)
With ever increasing social and environmental problems, the principles of Socio-Economic Sustainable development have gained prime importance. Human activities and their after-effects, direct and indirect, strongly influence nature and its resources. Keeping the huge role played by mankind in sustaining the glory of nature in mind, development goals need to be shaped in accordance with the parallel development and benefit of nature. India, as a developing nation, has a landmark role to play in future ecology conservation and management.